When should we use diagnostic imaging to investigate for pulmonary embolism in pregnant and postpartum women?. Issue 1 (9th July 2014) - Goodacre, Steve; Nelson-Piercy, Catherine; Hunt, Beverley; Chan, Wee-Shian
Abstract : Pulmonary embolism (PE) is a leading cause of death in pregnancy and postpartum. Clinicians face a difficult choice when deciding whether to use diagnostic imaging to investigate for suspected PE in these patients, between risking potentially catastrophic consequences of missed diagnosis if imaging is withheld and risking unnecessary iatrogenic harm to both mother and fetus if imaging is overused. This paper explores the options for imaging and evidence for the use of clinical features, clinical predictions scores or biomarkers to select pregnant and postpartum women for imaging. It also considers where future research could be most appropriately directed.